2005
DOI: 10.1364/ao.44.003358
|View full text |Cite
|
Sign up to set email alerts
|

Ion-exchanged glass waveguides with low birefringence for a broad range of waveguide widths

Abstract: Optical communications networks require integrated photonic components with negligible polarization dependence, which typically means that the waveguides must feature very low birefringence. Recent studies have shown that waveguides with low birefringence can be obtained, e.g., by use of silica-onsilicon waveguides or buried ion-exchanged glass waveguides. However, many integrated photonic circuits consist of waveguides with varying widths. Therefore low birefringence is consequently required for waveguides ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…Bimodal behavior, checked by the CCD camera, appears for waveguides with diffusion aperture wider than 4 μm. This figure shows that the birefringence increases with the width of the waveguide diffusion aperture, as already reported in [9].…”
Section: B Experimental Measurements 1) Homogeneous Buried Waveguidesupporting
confidence: 87%
See 2 more Smart Citations
“…Bimodal behavior, checked by the CCD camera, appears for waveguides with diffusion aperture wider than 4 μm. This figure shows that the birefringence increases with the width of the waveguide diffusion aperture, as already reported in [9].…”
Section: B Experimental Measurements 1) Homogeneous Buried Waveguidesupporting
confidence: 87%
“…Using Eq. (4), these results lead to a relatively low value of modal birefringence (ΔN = 5.01·10 −4 and ΔN = 4.99·10 −4 ), as expected for such buried waveguide [9].…”
Section: B Experimental Measurements 1) Homogeneous Buried Waveguidesupporting
confidence: 61%
See 1 more Smart Citation
“…The waveguides were fabricated into BGG31 glass by molten salt ion exchange followed by a burial process [9,10]. Aluminoborosilicate glass BGG31 was specifically developed to fulfill the requirements of ion-exchanged waveguides in passive (i.e., undoped) glass [11].…”
Section: Low Birefringence Waveguides In Aluminoborosilicate Glassmentioning
confidence: 99%
“…9 We have recently shown that the fundamental mode of ion-exchanged waveguides can have very low birefringence for waveguides with widely varying widths. 10 Values of the order of 10 Ϫ6 were measured when the burial process was followed by thermal annealing. However, we were not able to measure the birefringence for the odd mode and no waveguide grating was included.…”
Section: Introductionmentioning
confidence: 99%